HUBUNGAN PENGETAHUAN MANAJEMEN BERBASIS SEKOLAH DAN KECERDASAN EMOSIONAL DENGAN KINERJA KEPALA SEKOLAH DASAR DI KOTA BEKASI - Maisaroh Maisaroh; Ibnu Muthi (Jurnal Kinerja, 2023)
The aim of this research is to determine the relationship between school-based management knowledge, emotional intelligence together with the performance of private target school principals in Bekasi City. The research method used was quantitative in the form of a descriptive study with a sample of 173 teachers selected randomly from 12 school sub-districts. Data collection is carried out by distributing questionnaires or questionnaires. The data analysis used was descriptive statistics, multiple correlation coefficient, coefficient of determination and regression analysis with the help of SPSS version 20. The research results showed that there was a significant relationship between school-based management knowledge, emotional intelligence and the performance of private elementary school principals in Bekasi City. This means that together the variables of school-based management knowledge and emotional intelligence make a major contribution to the principal's performance variables.